Fibrosis and carcinoid syndrome: from causation to future therapy. - Druce, M; Rockall, A; Grossman, AB (2009)
Carcinoid tumors are part of a heterogeneous group of gastrointestinal and pancreatic endocrine tumors that are characterized by their capacity to produce and secrete hormones, 5-hydroxytryptamine, tachykinins and other mediators. These substances are thought to be responsible for the collection of symptoms, which include diarrhea, flushing and wheezing, that is known as carcinoid syndrome. Fibrosis that occurs either local to or distant from the primary tumor is one of the hallmarks of carcinoid tumors that originate from the midgut. The fibrotic process can occur in the mesentery as a desmoplastic response and may lead to obstruction of the small bowel, but it can also occur in the lungs, skin or retroperitoneum. Importantly, up to one-third of patients develop cardiac valvulopathy. One or more products that are secreted by the tumor and enter into the circulation are likely to have a role in this process. This Review discusses the incidence and prevalence of fibrosis in carcinoid syndrome and explores evidence to date for causative agents, in particular the roles of 5-hydroxytryptamine and elements of the downstream signaling pathway. Improved understanding of the etiology of carcinoid-tumor-related fibrosis may lead to better treatments for this condition than those we currently have.